Natural Products via Enzymatic Reactions - Piel, Jörn (Topics in Current Chemistry, 2010)
Key Building Blocks via Enzyme-Mediated Synthesis, by Thomas Fischer and Jörg Pietruszka * Engineered Biosynthesis of Plant Polyketides: Structure-Based and Precursor-Directed Approach, by Ikuro Abe * Enzymatic and Chemo-Enzymatic Approaches Towards Natural and Non-Natural Alkaloids: Indoles, Isoquinolines, and Others, by Joachim Stöckigt, Zhong Chen, and Martin Ruppert * Chemoenzymatic and Bioenzymatic Synthesis of Carbohydrate Containing Natural Products, by Bohdan Ostash, Xiaohui Yan, Victor Fedorenko, and Andreas Bechthold * Total (Bio)Synthesis: Strategies of Nature and of Chemists, by Alexandra A. Roberts, Katherine S. Ryan, Bradley S. Moore, and Tobias A.M. Gulder  .